That All Might Proclaim: Continuing Luther's Legacy of Access. Issue 2 (June 2017) - Hannan, Shauna
Abstract: This article proposes that the next century of Lutheranism focus on equipping the priesthood of all believers to proclaim. Access was one of Martin Luther's central reforms and continues to be a hallmark of the Lutheran church. However, access to the pulpit has not gone far enough. For the sake of the gospel, a robust movement toward homiletical education for the laity must accompany a movement toward lay preaching.